Balance test results in different hormonal statuses of the menstruation cycle. Are females more susceptible to lower extremities injuries on different days of their menstruation cycles? - Baghdadabad, M. B.; Mohaghegh, S. (Physical Therapy in Sport, 2024)
Background The Star Excursion Balance Test (SEBT) and its modification(mSEBT) as dynamic tests have been shown to have high reliability and validity for the prediction of lower extremities injuries including ACL ones. No previous study has compared mSEBT performance measures in different hormonal statuses of the menstrual cycle in naturally menstruating women. So aim of the study was comparison of mSEBT performance measures in days of the menstruation cycle with the peak of estrogen and progesterone hormones in naturally menstruating women.